Peran Pembiayaan Perbankan Syariah terhadap Usaha Mikro Kecil dan Menengah di Masa Pandemi Covid-19 (Studi Kasus pada BSI Kota Bengkulu) - Fransiska, Linda; Isnaini, Desi; Oktarinah, Amimah (Institut Agama Islam Bengkulu, 2021)
This study aims to determine the role of financing for the indonesian syariah bank in the city of Bengkulu in rescheduling, reconditioning, and restructuring of micro, small and medium business customers during the covid-19 pandemic, the research method used is qualitative methods. This type of research includes field research because it directly gets data from the field to find out the real situation. When the research took place at the beginning of September 2020-March 2021 and located at the Bank Syariah Indonesia branch office of S. Parman 2. This research is descriptive and uses two data, namely primary data and secondary data, where the primary data is obtained from Bank Syariah Indonesia Bengkulu city and secondary data obtained from notes, books, website publications, journals, articles, theses, and others. Data collection using three methods, namely observation so that it is directly aimed at the Bank Syariah Indonesia Bengkulu city, interviews to ask questions and answers, and documentation such as archives, reports, and so on. The results of the study are that in addition to still providing financing to customers during the covid-19 period, in rescheduling, the role of the bank is to provide an extension of the payment period, while in reconditioning. MSME customers affected by covid-19 can submit a restructuring application letter, but with the agreement of the two parties who are equally willing, and so is the restructuring, with is the conversion of a financing contract, where MSME customers are given any installment payment relief they can for 1 year.